Robot-Assisted Radical Cystectomy in the Management of Bladder Cancer - Jessica L. Keim; Dan Theodorescu (The Scientific World Journal, 2006)
The application of robotic technology to laparoscopic surgery has the potential to revolutionize the entire field of urology. The use of robotic-assisted radical cystectomy has been demonstrated in the literature only within the past 3 years, as much of the reconstruction and urinary diversion techniques associated with radical cystectomy are considered more technically challenging than other procedures. Here we review the available literature pertaining to this procedure, which consists of a limited number of case reports, case series, and pilot or feasibility studies. While theses results seem to point towards less blood loss, lower transfusion rates, and shorter hospital stays compared to open radical cystectomy, definitive conclusions and recommendations cannot yet be made because of a lack of larger and/or prospective studies or randomized trials.